c-Met overexpression in breast cancer with positive axillary lymph node - Hasanah, Huswatun; Masadah, Rina; Nelwan, Berti J.; Achmad, Djumadi; Miskad, Upik A.; Rahawarin, Halidah; Zainuddin, Andi A. (International Journal of Research in Medical Sciences, 2019)
Background: Breast cancer is the second most common cancer in the world and is the most epidemic cancer in women, with approximately 1.67 million cases. Metastasis of tumor cells to other organs is a major cause of the increasing trend of mortality in breast cancer. This study aims to analyze the expression of c-Met associated with metastasis to axillary lymph nodes in invasive breast cancer. Method: The research was conducted at the Laboratory of Anatomical Pathology of Hasanuddin University Hospital. Stratified sampling was performed from January 2014 - January 2019. Immunohistochemical staining technique was applied upon 66 collected samples, followed by evaluating the c-Met expression score in invasive breast cancer group with positive and negative lymph node status. Result: c-Met overexpression was found among the invasive breast cancer incidence with lymph node metastasis. Among 50 cases with c-Met overexpression (c-Met positive), 40 cases (80%) of invasive breast cancer with lymph node metastasis were identified, while 10 cases (20%) were found in invasive breast cancer without metastasis to lymph nodes. On 16 cases with negative c-Met, 3 cases (18.8%) were found in invasive breast cancer with lymph node metastasis, and 13 cases (81.3%) in invasive breast cancer without metastasis to the lymph nodes. The statistical test results indicated a significant correlation between c-Met expression scores and metastasis to axillary lymph nodes in invasive breast cancer (p <0.001). Conclusion: As one of biomarkers, c-Met overexpression plays a vital role in the treatment of patients with invasive breast cancer to predict patient outcomes and to determine modalities. It is possible to apply c-Met overexpression to investigate aggressiveness of metastatic tumor cells in the future.